2018
DOI: 10.3390/ijerph15020279
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variability of Anthropogenic and Natural Factors Influencing Groundwater Quality Based on Source Apportionment

Abstract: Globally, groundwater resources are being deteriorated by rapid social development. Thus, there is an urgent need to assess the combined impacts of natural and enhanced anthropogenic sources on groundwater chemistry. The aim of this study was to identify seasonal characteristics and spatial variations in anthropogenic and natural effects, to improve the understanding of major hydrogeochemical processes based on source apportionment. 34 groundwater points located in a riverside groundwater resource area in nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Groundwater Fe concentration showed a considerably decrease from 2006 ( Figure 3e) to 2016 ( Figure 3f) and this change corresponded with the results of Sharma, et al [59] and the Kruskal-Wallis test (Table 4) It has been reported that high contents of Fe and Mn in groundwater are common in northeastern China, with high Fe concentrations generally occurring where Mn concentrations are high [55][56][57]. Especially in the center of the Songnen Plain, in which our study area occurs, contents of Fe and Mn are as high as 11.2-44.4 mg/g and 0.5-1.0 mg/g, respectively, due to the abundance of iron-manganese nodules in local Quaternary aquifer sediments [55,58]. Therefore, the background concentrations of Fe and Mn in the study area are very high and usually exceed the acceptable levels.…”
Section: Groundwater Geochemical Characteristicsmentioning
confidence: 91%
“…Groundwater Fe concentration showed a considerably decrease from 2006 ( Figure 3e) to 2016 ( Figure 3f) and this change corresponded with the results of Sharma, et al [59] and the Kruskal-Wallis test (Table 4) It has been reported that high contents of Fe and Mn in groundwater are common in northeastern China, with high Fe concentrations generally occurring where Mn concentrations are high [55][56][57]. Especially in the center of the Songnen Plain, in which our study area occurs, contents of Fe and Mn are as high as 11.2-44.4 mg/g and 0.5-1.0 mg/g, respectively, due to the abundance of iron-manganese nodules in local Quaternary aquifer sediments [55,58]. Therefore, the background concentrations of Fe and Mn in the study area are very high and usually exceed the acceptable levels.…”
Section: Groundwater Geochemical Characteristicsmentioning
confidence: 91%
“…Major ions of river water and groundwater show higher concentrations in the dry season than in the wet season, including Ca 2+ , Na + , Mg 2+ , HCO 3 − , SO 4 2− , Cl − , and TDS (Table S1). This is caused by strong seasonal evaporation, slow groundwater runoff with weaker water‐rock interaction in addition to some influences from human activities in the dry season (Hulan Water Authority ; Zhang et al ; Guo et al ).…”
Section: Resultsmentioning
confidence: 99%
“…The comparative medium coefficient of variation (CV) for all PHEs showed a fairly large geochemical variability in concentrations for each of two metals in the sampled soils. Generally, the degree of variation can be divided into three levels: CV < 10% is considered as weak variability, 10% < CV < 100% defines moderate variability, and CV > 100% is strongly variable [ 38 , 39 ]. The CV of all PHEs at An'xi was moderate variability, following an order of Cr > Cd > Pb > As > Hg, which indicated the concentration of elements showing moderate geochemical variation.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the degree of variation can be divided into three levels: CV , 10% is considered as weak variability, 10% , CV , 100% defines moderate variability, and CV . 100% is strongly variable [38,39]. The CV of all PHEs at An'xi was moderate variability, following an order of Cr .…”
Section: Descriptive Statisticsmentioning
confidence: 94%